2013
DOI: 10.1038/ajg.2013.302
|View full text |Cite
|
Sign up to set email alerts
|

Cold Snare Polypectomy Vs. Cold Forceps Polypectomy Using Double-Biopsy Technique for Removal of Diminutive Colorectal Polyps: A Prospective Randomized Study

Abstract: CSP is superior to CFP for the endoscopic removal of DCPs with regard to completeness of polypectomy. CSP technique should be considered the primary method for endoscopic treatment of polyps in the 4-5-mm size range (ClinicalTrials.gov number: NCT01646242).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
211
3
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(222 citation statements)
references
References 23 publications
6
211
3
2
Order By: Relevance
“…This agrees with previous studies which found a higher rate of residual lesions after CFP of larger polyps [10,11]. Interestingly, we found that the risk of recurrence was higher after CFP of diminutive right colonic polyps than left colonic ones.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This agrees with previous studies which found a higher rate of residual lesions after CFP of larger polyps [10,11]. Interestingly, we found that the risk of recurrence was higher after CFP of diminutive right colonic polyps than left colonic ones.…”
Section: Discussionsupporting
confidence: 93%
“…Several recent studies examined microscopically the presence of residual lesions after CFP by observing specimens obtained immediately by biopsy or endoscopic mucosal resection of post-CFP ulcer edges. The incomplete resection rate ranged from 8 to 38 % [8][9][10][11]. Although these studies revealed a high rate of incomplete resection immediately after CFP of diminutive polyps, that does not necessarily mean that this rate is exactly the same as the real adenoma recurrence rate during follow-up because mechanical disruption of microvasculature and intercellular cohesiveness by CFP could theoretically lead to a loss of residual adenoma tissue.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…After endoscopic resection, the margins of the polypectomy defect should be carefully inspected to ensure the complete removal of all visible pathological tissue. Methods to assess and document complete resection at the time of polypectomy have not been determined, although the taking of biopsies from the base and edges of the polypectomy site is widely used [9,28]. In one study, endoscopic mucosal resection of the polyp base was the method of evaluation of complete resection [10].…”
Section: Discussionmentioning
confidence: 99%